Vision Boards: Students Look Into Their Futures. (3rd April 2021) - Conderman, Greg; Young, Natalie
Abstract: To prepare for college and careers, students at all grade levels can begin identifying the course for their futures. By incorporating purposeful activities, teachers can give students opportunities to visualize and state their future goals.